English Language Teaching in India: A Review - Kataria, Sonia (Journal of Advanced Research in English & Education, 2021)
English in India is a symbol of people’s aspirations for quality in education and a fuller participation in national and international life. The visible impact of this presence of English is that it is today being demanded by everyone at the very initial stage of schooling. ELT in India is vibrant and dynamic today. The context of the whole teaching paradigm has changed totally. This article traces the course of this change, along with the causes and consequences while comparing this with the course of ELT in other contexts where it has always been a first language. How to cite this article:  Kataria S. English Language Teaching in India: A Review. J Adv Res Eng & Edu 2020; 5(4): 19-21.